2012
DOI: 10.1111/j.1399-5618.2012.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based options for treatment‐resistant adult bipolar disorder patients

Abstract: Most studies identified were small, involved supplementation of typically complex ongoing treatments, varied in controls, randomization, and blinding, usually involved brief follow-up, and lacked replication. Clearer criteria for defining and predicting treatment resistance in BD are needed, as well as improved trial design with better controls, assessment of specific clinical subgroups, and longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 89 publications
0
36
0
Order By: Relevance
“…Despite the limited magnitude of risk conferred by CACNA1C rs1006737 at the individual level, this polymorphism is robustly and consistently associated with BD. As L-type voltage gated calcium channels already exist as a pharmacological approach targeting Ca v 1.2, this presents an appealing avenue of investigation that warrants a second look after initially disappointing findings (Poon et al, 2012). With the goal of moving towards personalized medicine, research focusing on identifying sub-groups that show a more marked response to CCBs may be warranted.…”
Section: Summary and Future Directionsmentioning
confidence: 97%
“…Despite the limited magnitude of risk conferred by CACNA1C rs1006737 at the individual level, this polymorphism is robustly and consistently associated with BD. As L-type voltage gated calcium channels already exist as a pharmacological approach targeting Ca v 1.2, this presents an appealing avenue of investigation that warrants a second look after initially disappointing findings (Poon et al, 2012). With the goal of moving towards personalized medicine, research focusing on identifying sub-groups that show a more marked response to CCBs may be warranted.…”
Section: Summary and Future Directionsmentioning
confidence: 97%
“…Other treatments for bipolar depression remain experimental or lack regulatory approval (Poon 2012;. We discuss those with the most developed evidence in this section.…”
Section: Experimental Treatmentsmentioning
confidence: 99%
“…The possible value of other pharmacological treatments has been considered, including calcium channel blockers, anticholinesterases, omega-3 fatty acids and other 'nutriceuticals', as well as exogenous thyroid hormones, but they require further testing in bipolar depression (Poon 2012). Promising findings have been recently reported for the glutamate N-methyl-d-aspartate receptor antagonist ketamine, which is inconvenient to administer (orally inactive) and short-acting.…”
Section: Other Pharmacological Treatmentsmentioning
confidence: 99%
“…A systematic review that included 15 clinical trials showed that clozapine was associated with improvement in social functioning [23]. It is worth mentioning that clozapine may be also effective for treatment-resistant patients with bipolar disorder [23][24][25]. Despite proven effectiveness in bipolar disorder, there are concerns regarding some significant side effects, including agranulocytosis, myocarditis, cognitive disturbances, and weight gain.…”
Section: Functioning and Neurocognitive Impairmentmentioning
confidence: 99%